Association between lung function and hypertension and home hypertension in a Japanese population: the Tohoku Medical Megabank Community-Based Cohort Study. Issue 3 (3rd March 2023) - Takase, Masato; Yamada, Mitsuhiro; Nakamura, Tomohiro; Nakaya, Naoki; Kogure, Mana; Hatanaka, Rieko; Nakaya, Kumi; Chiba, Ippei; Kanno, Ikumi; Nochioka, Kotaro; Tsuchiya, Naho; Hirata, Takumi; et al.
Abstract : Background: Although several studies have shown an inverse association between lung function and hypertension, few studies have examined the association between lung function and hypertension among never-smokers, and no study has investigated the association between lung function and home hypertension. We investigated the associations between lung function and hypertension in a Japanese population. Individuals and methods: We conducted a cross-sectional study of 3728 men and 8795 women aged 20 years or older living in Miyagi Prefecture, Japan. Lung function was assessed using forced expiratory volume at 1 s (FEV1 ) and forced vital capacity (FVC), measured by spirometry. Hypertension was defined as a casual blood pressure at least 140/90 mmHg and/or self-reported treatment for hypertension. Home hypertension was defined as morning home blood pressure at least 135/85 mmHg and/or self-reported treatment for hypertension. Multivariate logistic regression models adjusted for potential confounders were used to assess the association between lung function and hypertension. Results: The mean ages (±SD) of men and women were 60.1 (±14.0) years and 56.2 (±13.4) years, respectively, and 1994 (53.5%) men and 2992 (34.0%) women had hypertension. In the multivariable models, FEV1 and FVC were inversely associated with hypertension. Inverse associations between lung function and hypertension were observed even among never-smokers. Furthermore, reduced lung function was associated with higher prevalence of home hypertension in men and women. Conclusion: Reduced lung function was associated with higher prevalence of hypertension, independent of smoking status. Assessment of the lung function or blood pressure may be required in individuals with reduced lung function or hypertension.